Computing with SN P systems with I/O mode - Adorna, Henry N. (Journal of membrane computing, 2020)
P systems were introduced more than two decades ago by Gheorghe Pǎun. They are known as nondeterministic maximally parallel computing models. Most of their variants are proved to be capable of solving NP problems in polynomial time. This work focuses on using neural-like P systems to simulate uniform sequential computing models. In particular, we consider a so-called Spiking Neural P module (SN P module) computing finite-state functions. We define and characterize a so-called (SN) P automatic sequence by SN P modules.